Economic assessment of flexible power generation from biogas plants in Germany's future electricity system. (February 2020) - Lauer, Markus; Leprich, Uwe; Thrän, Daniela
Abstract: When integrating intermittent renewable energies in the electricity system, additional technologies are needed to ensure that a sufficient power supply is maintained. Alongside storage technologies and conventional power plants, dispatchable biogas plants are one solution for balancing demand and supply in energy systems with a high proportion of renewable energies. In this study, we conducted an economic assessment of the different extension paths and modes of operation of the biogas plants in Germany's future electricity system for the period of 2016–2035. This entailed carrying out a cost-benefit analysis that included the costs incurred for the flexibilization and installation of new biogas plants and the costs saved with respect to onshore wind turbines and additional saved opportunity costs. The results show that adding biogas plants in Germany's future electricity system –compared to their phase-out– requires cost reductions and/or has to be accompanied by further benefits in other sectors and areas to ensure economically feasible operation. Differentiated from a substantial growth, higher net present values were obtained in the extension path characterized by a low construction rate of new biogas plants. Furthermore, the economic feasibility of biogas plants benefits from an early phase-out of lignite- and coal-fired power plants. Highlights: Biogas plants were assessed economically in Germany's future electricity system. Adding biogas plants requires further benefits to ensure economic feasibility. Higher net present values were found when the rate of new biogas plants was low. Power generated from biogas plants should be as flexible as possible. An early phase-out of conventional power plants improves the economic feasibility.